Chronic toxicity of polystyrene nanoparticles in the marine mussel Mytilus galloprovincialis - Gonçalves, Joanna M. (2021)
Nanoplastics (NP) (1–100 nm) are a growing global concern, and their adverse effects in marine organisms are still scarce. This study evaluated the effects of polystyrene nanoplastics (10 μg/L; 50 nm nPS) in the marine mussel Mytilus galloprovincialis after a 21 – day exposure. The hydrodynamic diameter and zeta potential of nPS were analysed, over time, in seawater and ultrapure water. A multibiomarker approach (genotoxicity (the comet assay) was assessed in mussel haemocytes, and the antioxidant enzymes (superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPx)), biotransformation enzyme (glutathione – S – transferase (GST)), and oxidative damage (LPO)) was assessed in gills and digestive glands to evaluate the toxicity of nPS towards mussels. In seawater, aggregation of nPS is favoured and consequently the hydrodynamic diameter increases. Genotoxicity was highly noticeable in mussels exposed to nPS, presenting a higher % tail DNA when compared to controls. Antioxidant enzymes are overwhelmed after nPS exposure, leading to oxidative damage in both tissues. Results showed that mussel tissues are incapable of dealing with the effects that this emerging stressor pursues towards the organism. The Integrated Biomarker Response index, used to summarise the biomarkers analysed into one index, shows that nPS toxicity towards mussels are both tissue and time dependent, being that gills are the tissue most compromised.